Superficial mycosis profile in the Tertiary Hospital Dr. Moh. Hoesin Palembang: retrospective research - Desi Harnis; Rusmawardiana; , Fifa Argentina (Jurnal RSMH Palembang, 2020)
Background Superficial mycoses is a fungal infection of the skin, nails and hair thatcaused by dematophytes, yeast and mold. Superficial mycoses infections are commonlyfound in high temperature and humidity area such as Indonesia. Palembang is one ofregions in Indonesia has a high temperature and humidity, considered the incidenceof this disease is high. A retrospective study of new cases of superficial mycoses, datataken from medical records and register book at Policlinic of Dermatology andVenereology Dr. Moh. Hoesin Palembang during 5 years from January 2014-December2018. There were 1,236 (17.1%) new cases of superficial mycoses. Incidence ofsuperficial mycoses varies with range 6.9%-23%. The most common superficialmycoses is dermatophytes (38,3%). Microsporum canis, Trichophyton rubrum danTricophyton hmentagrophytes are frequent isolates in this study. The most age groupis 36-45 years (17.6%) with male more than female. Superficial mycoses are often foundin students (26.9%), followed by unskilled workers (20.8%). Of the 1,236 new cases,125 patients had comorbidities, such as malignancy 21 (16.8%) patients,cerebrovascular disease and diabetes mellitus each 16 patients (7.4%). Inguinal andabdomen are the most commonly infected regions. 656 (53.1%) patients was giventopical antifungal. The most common topical antifungal was ketoconazole 2% cream(62%) and systemic antifungal was itraconazole (55,3%).Conclusion: Cases ofsuperficial mycoses, especially dermatophytosis and Malassezia were still commonlyfound, especially in Palembang.